Interaksi simbolik pengguna aplikasi dating online bumble di Indonesia (Jurnal Kajian Media, 2021)
In this era of technological development, social media provides convenience in social interactions that affect social relationships. From making new friends, work relationships to finding a partner. During this pandemic, online dating is chosen as an alternative to finding a partner, whether for a serious relationship or just looking for friends. Bumble is an alternative virtual dating that can be used to make a close friend from cyberspace. The aims of this research to find out how communication is built to create an impression through the meaning of text messages in order to get a match or communication participant. This research uses a descriptive qualitative method with a case study approach. The result of this research is that the communication activities carried out by informants to build an impression on their "match" through text messages tend to use attarction-seeking strategies and have the goal of being admired. However, their “match” partner instead uses a self-controlling strategy that aims to conceal error by providing information that does not match reality. Which is included in fraud in social media or can be called Deception in Computer-Mediated Communication. Keywords: Online Dating, Bumble, Communication Activities, Building Impressions, Deception in Computer-Mediated Communication.